Facing Anxiety through Ego Defense Mechanisms on The Walking Dead: Michonne Movie Game - Fery Setiawan; I Gusti Agung Sri Rwa Jayantini; Ida Bagus Gde Nova Winarta; Ni Komang Arie Suwastini (Journal of Language and Literature, 2021)
With the advancement of technology, a newly adopted form of literary work was found, known as a movie game. It is one of the game genres that resembles real movies that provide choices to the players who can actively determine the story, ending, and characters' action. In literary work, a character is one of the intrinsic elements that can be interestingly analyzed from the psychological perspective, including Ego Defense Mechanisms. This study focuses on how the protagonist in a movie game entitled The Walking Dead: Michonne faced her anxiety through her ego defense mechanisms. It aims to identify the types of ego defense mechanisms and how they can help the protagonist cope with her anxiety. The discussion was based on psychoanalysis theory, namely Ego Defense Mechanisms proposed by Sigmund Freud. This study elaborated the description of the protagonist's actions when she faced anxiety through a qualitative method. The analysis revealed that the protagonist adopted the four types of Ego Defense Mechanisms: repression, sublimation, rationalization, and aggression. It was found that aggression was the most frequently adopted mechanism, followed by sublimation, rationalization, and the least was repression. This finding indicated that the protagonist chose aggression to release resentment or dissatisfaction, especially when facing objects or other characters that create anxiety or frustration. It implies that the persistence of aggression, sublimation, rationalization, and repression could reflect the presence of continual threats in the environment from which people should survive.